INFLUENCE OF INFORMATION TECHNOLOGY, RELIABILITY AND CHARACTERIZATION OF MANAGEMENT ACCOUNTING SYSTEM (MAS) ON MANAGERIAL PERFORMANCE WITH TRUST ON TECHNOLOGY OF ACCOUNTING INFORMATION SYSTEMS AS MODERATING VARIABLES (EMPIRICAL STUDY IN INSURANCE COMPANIE - putri, yolla indahwati (International Journal of Public Budgeting, Accounting and Finance, 2018)
Good managerial performance is obtained through a provision of good information as well. The existence of good information obtained through many factors. Factors that can provide good information for the company are information technology, interdependence, and the characteristics of the system. Given these factors enabled the manager will be able to make good decisions as well so that ultimately improve managerial performance. But besides that, the existence of the trust factor on the accounting information system technology can also provide a strong influence on the relationship between the factors mentioned above. This study aims to investigate the influence of information technology, interdependence, and the characteristics of management accounting systems to managerial performance with confidence on accounting information systems technology as a moderating variable. This type of research is a quantitative study using census method. The population in this study were employees of insurance companies in IT are registered in the General Insurance Association of Indonesia Branch field. Data collection techniques by distributing questionnaires. The data used is primary data in the form of answers from respondents. Before testing the first hypothesis testing data quality in the form of test validity and reliability testing. Then performed classical assumption. Hypothesis testing using the F test Overall the independent variables significantly influence managerial performance. While confidence in the technology information accounting system can do serve as a moderating variable that affects the relationship between the independent variable on the dependent variable.